2019
DOI: 10.1016/j.optcom.2019.04.088
|View full text |Cite
|
Sign up to set email alerts
|

Quantum teleportation of qudits by means of generalized quasi-Bell states of light

Abstract: Quantum superpositions of coherent states are produced both in microwave and optical domains, and are considered realizations of the famous "Schrödinger cat" state. The recent progress shows an increase in the number of components and the number of modes involved. Our work creates a theoretical framework for treatment of multicomponent two-mode Schrödinger cat states. We consider a class of single-mode states, which are superpositions of N coherent states lying on a circle in the phase space. In this class we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Multimode squeezed states exhibit a large interest for QIP applications, such as quantum state sharing, quantum teleportation and multipartite entangled states [47,89,90,115,116]. It was recently demonstrated that the affine quantization of the cosmological dynamics removes the classical singularity and univocally establishes a unitary evolution.…”
Section: Late Results and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimode squeezed states exhibit a large interest for QIP applications, such as quantum state sharing, quantum teleportation and multipartite entangled states [47,89,90,115,116]. It was recently demonstrated that the affine quantization of the cosmological dynamics removes the classical singularity and univocally establishes a unitary evolution.…”
Section: Late Results and Applicationsmentioning
confidence: 99%
“…Late progress and results illustrate that universal quantum computing (QC) can be generalized to multilevel qudits [90,91]. Trapped ions represent an example of a pristine environment that enables scientists to acquire excellent quantum control [42,43,48,[92][93][94][95], which makes them perfect candidates towards implementing qudit-based quantum information processing (QIP) [47,96,97].…”
Section: Generalized Squeezed States Applications For Ion Trapsmentioning
confidence: 99%
“…Повышенная различимость сопряженных двухмодовых состояний может значительно повысить вероятность успеха телепортации. В частности, удвоение когерентных состояний используется в протоколе квантовой телепортации на основе обобщенных квазибелловских состояний поля [29], и его замена на удвоение с сопряжением значительно увеличит вероятность успеха, особенно при малом среднем числе фотонов. В-третьих, применение сопряжения амплитуды к сжатым когерентным полям представляет интерес для более эффективной передачи многомодового квантового сигнала [30].…”
Section: вероятность различенияunclassified
“…A quantum particle can physically have many degrees of freedom, implying that a quantum system may have more than two dimensions. Researchers [26][27][28][29][30] have thus extended QT to operate in high dimensionally, both in theory and in practice. The authors in Ref.…”
Section: Introductionmentioning
confidence: 99%